2004
DOI: 10.1093/alcalc/agh071
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Self-Reported Drinking in Adolescence

Abstract: The adolescent drinking amount self-reports seem reasonably reliable and valid both on a population and individual level. A set of closed questions may capture the amount drunk even better than an open question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(114 citation statements)
references
References 34 publications
3
107
0
4
Order By: Relevance
“…This study showed that items relating to alcohol use and smoking for 15-year-old students have a good reliability, which is not surprising, as the finding is similar to previous studies on self-reported measures of adolescent drinking (Lintonen et al 2004) and smoking ). An explanation for this is the fact that substance use displays a certain degree of cross-time stability, and therefore it can be recalled more reliably than other health behaviours .…”
Section: Test-retest Reliability Of Selected Hbsc Survey Itemssupporting
confidence: 89%
“…This study showed that items relating to alcohol use and smoking for 15-year-old students have a good reliability, which is not surprising, as the finding is similar to previous studies on self-reported measures of adolescent drinking (Lintonen et al 2004) and smoking ). An explanation for this is the fact that substance use displays a certain degree of cross-time stability, and therefore it can be recalled more reliably than other health behaviours .…”
Section: Test-retest Reliability Of Selected Hbsc Survey Itemssupporting
confidence: 89%
“…While this issue cannot be completely resolved, the published literature on this topic suggests that self-reported alcohol consumption measures are reliable for use in statistical analyses (Del Boca and Darkes, 2003;Friesema et al, 2004;Lintonen et al, 2004;Townshend and Duka, 2002). Third, we are not able to examine the temporal order of events with gambling and alcohol use due to the cross-sectional nature of the NESARC data.…”
Section: Discussionmentioning
confidence: 90%
“…Most of the literature on the reliability of self-reports on sensitive topics has come from developed nations. [26][27][28] While some reports suggest acceptable reliability, others present lower scores. We do not know how far these reports from developed nations are applicable to a developing nation such as Zimbabwe.…”
Section: Discussionmentioning
confidence: 99%